Notes from and beyond my Conference Reading - Davey, Frank (Studies in Canadian Literature, 2007)
In introducing his most recent book, Back to the War (2005), Frank Davey reflects on the epistemological difficulties of contemporary poetry, and how his poems have become collections of irreconcilable propositions, or series of irreconcilable paragraphs themselves constructed of non sequiturs and abruptly changed viewpoints, or sets of multiple choice statements. His poetics in the past decade have become based on the concept of the proposition, specifically the proposition that language is for the most part propositional - offering more or less plausible constructions that are always alternative to other more or less plausible constructions.